Penerapan Arsitektur Berkelanjutan pada Pusat Pelatihan Usaha Mikro Kecil Dan Menengah (UMKM) di Kabupaten Bantaeng - Hasna, Hasna; Attar, Muhammad; Sam, Mukhlishah (TIMPALAJA : Architecture Student Journals, 2025)
The rapid development of Micro, Small, and Medium Enterprises (UMKM) in Indonesia highlights their vital role as the foundation of a people-driven economy capable of withstanding global economic fluctuations. Improving the quality and productivity of UMKM actors requires adequate training facilities that support the development of managerial and production skills. This study aims to examine the application of sustainable architecture principles in the design of an MSME Training Center in Bantaeng Regency to enhance the competence and independence of local entrepreneurs. The research employs a qualitative-descriptive approach, drawing on literature reviews, previous studies, field observations, and site analysis. The findings were synthesized into design concepts, form transformation strategies, and three-dimensional visualizations. Results indicate that sustainable architectural strategies—particularly energy efficiency achieved through optimized natural lighting and ventilation—create an environmentally friendly, functional, and climate-responsive building design. Site development prioritizes accessibility, comfort, and spatial efficiency to support comprehensive training activities. Overall, the sustainable design approach not only improves the building’s operational efficiency but also reinforces Bantaeng Regency’s position as an adaptive and progressive region in UMKM development.